'One of the Twelve' and Mark's Narrative Strategy - Yang, Jayhoon (2004)
Explores how Mark, the author and one of the twelve apostles, makes his narrator manipulate the reader by controlling the information about Judas Iscariot. Mark's reference to Judas; Explanation given by the Markan narrator regarding the reason for Jesus Christ for calling the twelve apostles; Modifications attributed to Judas; Influence of the negative characterization of Judas Iscariot on readers' negative perception of the twelve apostles in the last three pericope.
Keywords: Apostles; Bible. Mark; Christian saints; Jesus Christ -- Calling of the twelve; Narration (Rhetoric)